2020
DOI: 10.1088/2053-1591/ab7618
|View full text |Cite
|
Sign up to set email alerts
|

Spark plasma sintering plus heat-treatment of Ta-doped Li7La3Zr2O12 solid electrolyte and its ionic conductivity

Abstract: Ta-doped Li 7 La 3 Zr 2 O 12 (Ta-LLZO) solid electrolyte ceramics were synthesized by solid-state sintering, spark plasma sintering (SPS) and SPS plus heat-treatment (two-step method) using LiOH·H 2 O, La 2 O 3 , ZrO 2 and Ta 2 O 5 as the raw materials. The Ta-LLZO samples prepared from these three routes are all in cubic phase structure. However, the solid-state method results in Ta-LLZO samples with different particle sizes and porous morphology, while the samples prepared by SPS route contain fewer internal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…(SPS), [89][90][91][92] hot pressing (HP), [93][94][95][96] rapid sintering, [85,97] and field-assisted sintering technique (FAST), [98,99] much denser LLZO ceramic pellets could be produced (relative density more than 97% even better). [85,93] Schematic diagram of some special sintering methods are shown in Figure 3.…”
Section: Improving Ionic Conductivity and Relative Density Of Isesmentioning
confidence: 99%
See 1 more Smart Citation
“…(SPS), [89][90][91][92] hot pressing (HP), [93][94][95][96] rapid sintering, [85,97] and field-assisted sintering technique (FAST), [98,99] much denser LLZO ceramic pellets could be produced (relative density more than 97% even better). [85,93] Schematic diagram of some special sintering methods are shown in Figure 3.…”
Section: Improving Ionic Conductivity and Relative Density Of Isesmentioning
confidence: 99%
“…A relative density of ≈90% could be achieved by traditional high‐temperature sintering method. While using some special sintering methods, such as spark plasma sintering (SPS), [ 89–92 ] hot pressing (HP), [ 93–96 ] rapid sintering, [ 85,97 ] and field‐assisted sintering technique (FAST), [ 98,99 ] much denser LLZO ceramic pellets could be produced (relative density more than 97% even better). [ 85,93 ] Schematic diagram of some special sintering methods are shown in Figure .…”
Section: Strategies On Enhancing Performance Of Sses For Fast‐chargingmentioning
confidence: 99%
“…41 Recent works on lithium garnet solid-state electrolytes processed with advanced sintering techniques are summarized in Tables II-IV. 37,41,45,50,72,73,75,[80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97]…”
Section: Microstructure Modification Of Lithium Garnet Electrolytes T...mentioning
confidence: 99%
“…Xue et al reported a Ta-doped LLZO garnet ceramic by the SPS method with minimum interior voids and small grain size of the ceramic material. 107 The double step (SPS) sintering and sintering in the air made the garnet ceramic more compact and increased the particle size, exhibited ionic conductivity of 4.6 × 10 −3 S cm −1 at 423 K with activation energy 0.38 eV. 107 under sintering temperature 1173 K/30 min with a sintering rate of 323 K min −1 .…”
Section: Sintering Techniques For Garnet Type Solid Electrolytesmentioning
confidence: 99%
“…107 The double step (SPS) sintering and sintering in the air made the garnet ceramic more compact and increased the particle size, exhibited ionic conductivity of 4.6 × 10 −3 S cm −1 at 423 K with activation energy 0.38 eV. 107 under sintering temperature 1173 K/30 min with a sintering rate of 323 K min −1 . 98 The scheme of SPS is displayed in Figure 12.…”
Section: Sintering Techniques For Garnet Type Solid Electrolytesmentioning
confidence: 99%